The Effect Of Circuit Training On Cardiovascular Endurance In The Rasoex Cikarang Basketball Team - Pahlevi, Reza; Setiawan, Muhammad Arief; Dewi, R. Retna Kinanti; Wijaya, Habibi Hadi; Aulia, Dany (UNIVERSITAS NEGERI MAKASSAR, 2024)
Basketball is a sport that relies on individual skills and teamwork in attack and defence. One important component in the success of a basketball game is physical condition, especially cardiovascular endurance. Good cardiovascular endurance allows an athlete to maintain optimal physical performance in high-intensity matches. This study aims to examine the effect of Circuit Training on increasing cardiovascular endurance in the Rasoex Cikarang basketball team. The research method used is a quantitative approach with a Purposive Sampling technique involving 13 participants. The training program was carried out for 4 weeks with 16 training meetings carried out routinely. Before and after the training program, cardiovascular endurance was measured to determine the effect of training on its improvement. The data obtained were analyzed using SPSS 24 with the Paired T-Test to see the difference in cardiovascular endurance scores before and after training. The results showed that there was a significant increase in the cardiovascular endurance of participants, with an average increase of 7.43% after participating in Circuit Training. These findings indicate that Circuit Training can increase cardiovascular endurance capacity, which has a positive effect on the performance of basketball athletes, especially in facing high intensity during matches. Thus, Circuit Training can be an effective training method for improving the physical endurance of basketball athletes